Pencegahan dan Penanggulangan Hama Kumbang Tanduk Pasca Replanting Kelapa Sawit (Elaeis guineensis Jacq.) di Desa Bandur Picak Kecamatan Koto Kampar - Agriani, Feri; Boris Kaido; Sri Oktika Syahputri; Afdhal Afdhal; Nina Veronika; Nur Asma Deli; Agung Pramono; Tri Kurniaty; Dini Amalia Putri; Yogy Rasihen; Fajar Aga Wandana (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The Smallholder Oil Palm Replanting Program (PSR) is a key initiative to improve the productivity of Indonesia’s smallholder plantations. However, the replanting process increases the risk of pest attacks, particularly from rhinoceros beetles (Oryctes rhinoceros), which can damage the shoot apex, inhibit plant growth, and even cause the death of young oil palm trees. This community service activity was carried out in Bandur Picak Village, Koto Kampar Hulu Subdistrict, with the aim of educating and training farmers on Integrated Pest Management (IPM) strategies to control rhinoceros beetles. The methods included educational sessions, technical training, and field demonstrations on the use of pheromone traps, the application of the entomopathogenic fungus Metarhizium anisopliae, and the management of organic waste. The results showed that 85% of participants improved their understanding of pest biology and control techniques and expressed readiness to implement IPM practices in their fields. This activity effectively enhanced farmers’ capacity in environmentally friendly pest control and supported the success of oil palm replanting. Strengthening local capacities through participatory approaches is essential to achieving sustainable plantation management in rural areas.